2009
DOI: 10.1299/jmmp.3.529
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Support and Heat Dissipation in Thermal Stress Cleaving of Thin Glass Plates

Abstract: Numerical analysis was conducted to solve the problems encountered in the thermal stress cleaving of borosilicate-glass plate of 50µm thick using CO 2 laser with the speed over 100mm/s. We investigated the influence of constraint and the effect of heat dissipation from the surface. It is concluded that the constraint of out-of-plane deformation does not influence the distribution of thermal stress intensity factor in the thickness and higher cleaving velocity may be attained with increase of heat dissipation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…It is considered that the crack propagation behavior is controlled by the intensity factor of the maximum tangential stress, and the strength factors of the edge defects with different sizes are calculated by finite element simulation. In 2009, Motomura F et al [21,22] simulated the process of CO2 laser cutting glass and studied the influence of constraints, surface heat transfer, material thickness and other factors on laser heating temperature and glass fracture strength factor. The research results showed that the stronger the surface heat dissipation capacity, the closer the crack tip was to the center of heat source.…”
Section: Introductionmentioning
confidence: 99%
“…It is considered that the crack propagation behavior is controlled by the intensity factor of the maximum tangential stress, and the strength factors of the edge defects with different sizes are calculated by finite element simulation. In 2009, Motomura F et al [21,22] simulated the process of CO2 laser cutting glass and studied the influence of constraints, surface heat transfer, material thickness and other factors on laser heating temperature and glass fracture strength factor. The research results showed that the stronger the surface heat dissipation capacity, the closer the crack tip was to the center of heat source.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the crack propagation velocity varies considerably especially when the crack tip locates near the plate edges even when the laser heat source moves in a constant velocity. The crack propagation that follows a moving heat source can be treated quasi statically under the theory of thermo-elasticity and is analyzed quantitatively by finite element method [1][2][3][4][5][6]. In the present analysis a symmetrical cleaving problem of a rectangular plate is chosen as a numerical example.…”
Section: Introductionmentioning
confidence: 99%